BERTEOLOGI PASTORAL SAAT COVID-19 DI JEMAAT GMIST SENGGIGILANG BAHOI KABUPATEN SANGIHE - Yohan Brek; Pratiwi Anggraini Makansing; Silia Bawohang; Novalin Boham; Triska Kansil (Institut Agama Kristen Negeri Manado, 2021)
This study aims to describe the perception and practice of Pastoral Theology during the Covid-19 pandemic, and the research location is in the GMIST Senggigilang Bahoi congregation. The research method used in this study is qualitative with an ethnographic approach in which to describe and interpret the same pattern of values, behavior, beliefs and language of a cultural group. In addition, research also emphasizes the value-laden nature of research and seeks answers to questions that emphasize how social experiences are created and given meaning. The results of this study will be a contribution of thought in the development of pastoral services including the basic understanding of Pastoral Theology, namely the Command of the Lord Jesus and Willing to serve with Love. Effective Pastoral Services, and Implementation of cultural-based pastoral practices.